Susceptibility and resistance status of dengue vectors towards selected pyrethroids in Kota Bharu, Kelantan - Mokhtar, Amani Ahmad (2021)
In Malaysia, Aedes sp. plays a significant role in the transmissions of vector-borne diseases such as dengue, chikungunya, and Zika. Regular usage of household insecticide products and occasional fogging events mainly in residential areas have raised an issue on the Aedes susceptibility status against insecticides. The objective of the study was to evaluate the susceptibility and resistance status of Aedes sp. mosquitoes against pyrethroids in Panji, Kota Bharu, Kelantan. A total of 100 F1 generations of adult female Aedes sp. were tested following WHO bioassay guidelines against permethrin 0.75% and lambda-cyhalothrin 0.05%. In addition, PCR analysis at the specific alleles of F1534C and V1016G of the tested mosquitoes were carried out to determine the presence of kdr mutations. Determination of the Aedes mosquito composition at the sampling areas was also done. From the results obtained, Ae. albopictus was found at both localities; Panji, Kota Bharu and Kubang Kerian whereas Ae. aegypti can only be found in Panji, Kota Bharu. The population of Ae. aegypti in the Panji area was highly resistant against all insecticides tested (type I pyrethroid permethrin 0.75%, 18.41±1.74 & type II pyrethroid lambda-cyhalothrin 0.05%, 14.58±9.45). On the other hand, Ae. albopictus was moderately resistant against type II pyrethroid lambda-cyhalothrin 0.05% (93.82±3.01). However Ae. albopictus showed to be highly resistant against type I pyrethroid, permethrin 0.75% (87.79±2.76). The Kubang Kerian Ae. albopictus population was susceptible against lambda-cyhalothrin 0.05% (98.97±1.03) and resistant against permethrin 0.75% (90.72±3.01). From the PCR analysis, the population of Ae. albopictus in Kubang Kerian showed two different genotype groups, F/C1534 and susceptible F/F1534 genotypes. On the other hand, both genotype groups of F/C1534 and resistant C/C1534 were detected in the mosquito population of Ae. aegypti and Ae. albopictus in Panji, Kota Bharu respectively. While all Ae. aegypti samples showed the V/V1016 genotype. Based on this study, both the bioassay and the PCR analysis showed that the Aedes sp. population had developed resistance against the insecticides tested. However, a study on allele frequency to confirm the role of the kdr mutations as well as a study on metabolic resistance are needed towards the Aedes mosquito resistance against pyrethroid insecticide in the population.